Magnetic properties of the low-dimensional spin-1/2 magnet α-Cu2As2O7 - Arango, Yulieth Cristina; Vavilova, E.; Abdel-Hafiez, M.; Janson, O.; Tsirlin, A. A.; Rosner, H.; Drechsler, S.-L.; Weil, M.; Nénert, G.; Klingeler, Rüdiger; Volkova, O.; Vasiliev, A.; et al. (Physical review. B, Condensed matter and materials physics, 2011)
In this work, we study the interplay between the crystal structure and magnetism of the pyroarsenate α-Cu2As2O7 by means of magnetization, heat capacity, electron spin resonance, and nuclear magnetic resonance measurements as well as density functional theory (DFT) calculations and quantum Monte Carlo (QMC) simulations. The data reveal that the magnetic Cu-O chains in the crystal structure represent a realization of a quasi-one-dimensional (1D) coupled alternating spin-1/2 Heisenberg chain model with relevant pathways through nonmagnetic AsO4 tetrahedra. Owing to residual 3D interactions, antiferromagnetic long range ordering at TN≃10 K takes place. Application of the external magnetic field B along the magnetically easy axis induces the transition to a spin-flop phase at BSF∼1.7 T (2 K). The experimental data suggest that substantial quantum spin fluctuations take place at low magnetic fields in the ordered state. DFT calculations confirm the quasi-one-dimensional nature of the spin lattice, with the leading coupling J1 within the structural dimers. QMC fits to the magnetic susceptibility evaluate J1=164 K, the weaker intrachain coupling J′1/J1=0.55, and the effective interchain coupling Jic1/J1=0.20.
Gesehen am 18.03.2022
Im Titel sind die Zahlen 2 und 7 tiefgestellt